THE APPLICATION OF FAMILY APPROACH TOOLS IN A CASE OF PARAPLEGIA - Lima Abade, Hillary; de Oliveira Monteiro, Marivone; Lopes de Figueiredo, Mirela; Gonçalves Silva, Dinariam; Paula Ferreira Maciel, Ana; Cordeiro Muniz, Elisabete; Esméria Neta, Maria; Godinho Souto, Silvania; Cristiane Soledade Dias, Kátia; Antunes Teixeira, Nadine; Dias Prado, Ticiane; Sousa Pinheiro, Jeferson; et al. (Health and Society, 2026)
Objective: To describe the experience of applying family-centered care tools to a family that recently underwent a change in its family context with the arrival of a member who is fully dependent on care, as well as the interventions performed. Methods: A descriptive-narrative, qualitative study was conducted in the second half of 2022 by the Family Health Strategy team located in the municipality of Taiobeiras, Minas Gerais, Brazil. The family was chosen based on the identified needs of one of its members, who had a recent history of hospitalization, was bedridden, paraplegic, and had a colostomy. The instruments used were: Genogram, Ecomap, Life Cycle, FIRO (Fundamental Interpersonal Relations Orientations), P.R.A.C.T.I.C.E., and Family Conference. Final considerations: The approach made it possible to understand the family holistically, monitor and facilitate appropriate treatment for the patient, as well as strengthen the bond between the Family Health Strategy and the users. The study proved essential, providing information that coincides with the users’ experiences, also demonstrating the relevance of applying the tools, since this process reflects the evolution of the Brazilian health system, being indispensable in Primary Health Care for Families and Communities.